Obstetric violence and associated factors among women who gave birth at public hospitals in Addis Ababa city administration, Ethiopia - Simeneh, Getinet Tilahun; Tesema, Getaye Worku; Seifu, Befikad Assefa; Tafesse, Nebiyou; Hailemariam, Abemelek Zegeye; Suleyiman, Feruza Mehammed; Nigatu, Digafe Tsegaye (Frontiers in Global Women's Health, 2024)
BackgroundObstetric violence during labor and delivery is one of the main reasons that women do not seek care from health caregivers in health facilities. Developing respectful maternity care services for women is the most important approach to ensure better newborn and maternal outcomes.ObjectiveThis study aimed to assess the magnitude of obstetric violence and associated factors among women who gave birth at public hospitals in Addis Adaba city administration, Ethiopia.MethodsAn institution-based cross-sectional study was carried out among 409 mothers who had given birth at two public hospitals (Gandhi Memorial Hospital and Abebech Gobena Mothers and Children's Health Hospital) in Addis Ababa, Ethiopia, from 1 to 30 May 2023. A systematic sampling method was applied and data were collected using a structured face-to-face interview questionnaire and entered into EpiData 3.1. The data were analyzed using Statistical Package for Social Science version 25. Bi-variable and multivariate analyses were performed. Statistical significance was declared at a P-value <0.05.ResultsIn total, 318 mothers [77.8% with a 95% CI (73.64–81.96)] had experienced obstetric violence in the study settings. Being more educated [Adjusted Odds Ratio (AOR) = 6.43; 95% CI 2.92–14.17], having ≥4 antenatal care contacts (AOR = 3.59; 95% CI 1.91–6.75), being multiparous (AOR = 2.65; 95% CI 1.32–5.32), induction of labor (AOR = 3.39; 95% CI 1.69–6.79), vaginal delivery (AOR = 0.25; 95% CI 0.11–0.62), and female birth attendants AOR = 2.42, 95% CI (1.31–4.47) were significantly associated with obstetric violence.ConclusionMore than three-fourths of the participants experienced obstetric violence. Thus, stakeholders need to develop interventions by taking all risk factors of obstetric violence into account.